Caracteristicas fisiologicas em testes laboratoriais e resposta da concentracao de lactato sanguineo em tres lutas em judocas das classes juvenil- A, junior e senior - Franchini, E.; Takito, M. Y.; Perrout, J. R.; Haddad, S.; Peduti, M. A.; Regazzini, M.; Böhme, M. T. S. (Revista Paulista Educação Física, 1998)
The purpose of this study was to verify the relationship between physiological and metabolic variables measured in the laboratory and in fight situation and to compare both in Juvenile- A (15 to 17 yearsold), Junior (18 to 20 years- old) and Senior (more than 21 years- old) judo players. Tests were carried out in three different situations: treadmill test (TT); cycloergometer test for the upper limbs (CTUL); and fight situation (FS). From these tests, differences among the three groups were sought performed in: speed of the athlete at the anaerobic threshold (VLAn); heart rate correspondent to VLAn; peak oxygen uptake, peak blood lactate concentration and heart rate in CTUL; peak blood lactate concentration after every fight and rate of perceived exertion according to Borg's scale (1982). The main results were: a) significant inverse correlation between VLAn and peak blood lactate concentration after each fight; b) significant correlation between rate of perceived exertion and peak blood lactate concentration after fight 1 (r = 0. 8073; p < 0. 001); c) the Senior class (10. 2 ± 2. 7 mM) showed higher values of blood lactate concentration after CTUL when compared to the Juvenile- A class (6. 7 ± 1. 1 mM); d) judo players of the Junior class (17 ± 1) ended their third fight with rate of perceived exertion at higher level than those of the Juvenile- A class (13 ± 2); e) there were no significant differences concerning to VLAn, peak VO2 in the CTUL and blood lactate after FS, showing that physiologically these classes were very similar.